The construction of nationalist politics : the MHP, 1965-1980. - Erken, A (2013)
This thesis presents an analysis of the political discourse and strategies of the MHP (Milliyetçi Hareket Partisi-Nationalist Movement Party) between 1965 and 1980. It particularly focuses on the role of young militants in the development of the nationalist movement in Turkey during this period. The 1960s and 1970s in Turkey saw military coups, street clashes, violence perpetrated by university students, and the rapid proliferation of civil organizations. Yet this turbulent period in modern Turkish history has received no systematic historical investigation. The MHP was one of the principal actors of this period. The study argues that the change in the profile of the CKMP-MHP leadership and the recruitment of young nationalist students, who became increasingly involved in physical confrontations with the socialists, had multiple effects on nationalist discourse and strategies. Retired soldiers involved in the 27 May 1960 military coup sought to develop a nationalist party based on secular-Kemalist principles, but those people who held conservative views of nationalism started to join the CKMP-MHP. The anti-Republican discourse of this current of thought involved the re-appropriation of Ottoman history and culture and certain religious themes into nationalist discourse. This ideological orientation appealed to most of young nationalists organized around the ülkü ocakları. However, the thesis demonstrates that there were various channels of ideological indoctrination in the nationalist movement, a diversity of positions that sometimes stirred conflicts among the nationalists themselves. The question of political strategy involved paradoxical aspects as well. Young nationalists were willing to take on the mission of becoming the future elites of the country yet were simultaneously involved in violent confrontations with socialists. Most of the party leadership, on the other hand, was preoccupied with parliamentarian goals and the long-term administrative success of nationalist activists in the state apparatus. The thesis shows that viewing the party activities and paramilitary operations in the same framework gave rise to serious tensions within the nationalist movement. The findings of this study also shed light on the institutional and ideological evolution of the nationalist movement after 1980.